Development of a plasma activated multifunctional polyester fabric using zinc oxide nanoparticles and citronella oil microcapsules - Mehravani, Behnaz (2022)
There is a high demand for the development of textiles possessing multifunctional properties for outdoor, protective and health care applications. The coating of polyester (PES) textiles with metal nanoparticles and essential oils may act in a synergistic mode to obtain materials with improved antimicrobial and UV-protection properties. However, the lack of functional groups onto PES structure makes the adhesion of particles a difficult task. In this work, PES fabric was activated by dielectric barrier discharge (DBD) plasma treatment, and functionalized with zinc oxide nanoparticles (ZnO NPs) and poly (methyl methacrylate) (PMMA)-citronella microcapsules by dip-coating.